PERCEPTION OF VALUE AND QUALITY OF SERVICE TO CUSTOMER SATISFACTION AT COFFEE SHOP IN BANDAR LAMPUNG - Friska Oktavia; Susi Indriyani (Peradaban Journal of Economic and Business, 2022)
This study will determine if the perceived value and quality of service  affect customer satisfaction at Coffee Shop in Bandar Lampung. The research was conducted at ADIKSICAFE in Bandar Lampung. Researchers have collected from all available sources. All populations used were Coffee Shop visitors  and  100 samples were used. Validity and reliability tests, classical acceptance tests, hypothesis tests, IE f tests (simultaneous), t-tests (partial), determinant coefficient tests, and multiple linear regression analysis tests are performed as analytical methods.Based on the results, the impact of  perceived value and quality of service  has at the same time a positive and significant impact on customer satisfaction at Adiksi Cafe Bandar Lampung. Perceived value  has a partially positive and significant impact on customer satisfaction, and a quality of service impact has a partial positive and significant impact.